Pengendapan Torium (Th) dari Monasit Bangka Setelah Proses Solvent Impregnated Resin (SIR) - Prassanti, Riesna; Ani, Budi Yuli; Sumiarti; Dewita, Erlan (BRIN Publishing, 2019)
Alkaline processing of Bangka monazite is carried out through stages like decomposition; partial dissolution pH 3.7; partial precipitation pH 6.3; and total precipitation pH 9.8. These procesess produce sodium phosphate, Rare Earth (RE) Hydroxide, uranium (U), and thorium (Th). On decomposition procsess, 99 % of sodium phosphate had been recovered and RE Hydroxide was separated from U and Th with 85% recovery. Meanwhile, the U and Th products were still mixed so that needs to separate. Purification of Th from U in monazite had been carried out by using Solvent Impregnated Resin (SIR) method and continued by elution after SIR. The result is that Th is still in the liquid phase as thorium nitrate [Th(NO3)2] solution so it needs to be precipitated as thorium hydroxide [Th(OH)2] to facilitate the next process. Precipitation of Th after SIR process is conducted with the aim to obtain optimum precipitation condition. The supporting resin used is amberlite XAD-16 with impregnated tributyl phosphate (TBP) extractant, dilute nitric acid (HNO3) as elution reagent, and ammonium hydroxide (NH4OH) as precipitation reagent. The observed parameters are the effect of pH and precipitation time on Th recovery. The results show that the optimum precipitation conditions of Th from monazite after SIR process is on pH 1.2 and 60 minutes time, resulting recovery of 84.74 % Th, 3.26 % U, 34,74 % RE, and 8.52 % PO4.